PID control system implementation in embedded system for DC motor speed control - Ariff, Che Mohd Noor (2008)
This project is focused on implementation of the Proportional (P), Integral (I) and Derivative (D) control system algorithms in microcontroller unit (MCU) for direct current (DC) Motor speed control. The PlC series, P1C18F2331 has been used to perform the processing of PID algorithms for DC motor control purpose. The focus is on 12 volt DC motor with 30 revolutions per minute (rpm) maximum speed. No-load case and loaded case are the scope for this research. Three experiments have been done to look how much PID control algorithms affect the performances on driving actual DC motor; P1 algorithm experiment, PD algorithm experiment and PID algorithm experiment. The result shows that, implementation of PID algorithm in small scale MCU is possible. PID algorithm that has been implemented in MCU inside the DC motor controller module system can eliminate the steady state error and overshoot problem including settling time. By creating real time data acquisition software, the performance of the system is monitored and later on analyzed. It is later found out that the PID algorithm has been able to create faster settling time while the overshoot has been reduced to 5% and the steady-state has been successfully reduced. The impact of the load and no load application of the PID algorithm can be clearly seen by how the PID algorithm has helped the controller to drive a loaded DC motor to the desired speed which could not be achieved without the PID algorithm.